INTERVENSI MENGUNYAH PERMEN KARET DALAM MENGURANGI KELUHAN HAUS BERLEBIH DAN MENGATASI HIPERVOLEMIA PADA PASIEN HEMODIALISIS: STUDI LITERATUR - Anwar, I Made Dyanta; Antari, Gusti Ayu Ary; Astuti, Ika Widi (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023DO - 10.24843/coping.2023.v11.i06.p02, 2024)
Hypervolemia is a condition of fluid overload commonly experienced by kidney failure patients undergoing hemodialysis. Hemodialysis patients may experience rapid weight gain between dialysis sessions due to kidney function failure. This hypervolemia condition is exacerbated by excessive thirst complaints, leading hemodialysis patients to be non-compliant with fluid restrictions. Hypervolemia can lead to serious problems such as various hemodialysis complications and death. Therefore, one focus of hemodialysis patient care is managing thirst and hypervolemia. An alternative therapy that can be used is chewing gum. The problem formulation in this study uses the PICO method. Literature searches were conducted in databases such as Google Scholar, PubMed, and Science Direct. The keywords used were "Hemodialysis Patients AND chewing gum AND thirst." The inclusion criteria for this study were research using Randomized Controlled Trials (RCTs) and Quasi-experiments published from 2019 to 2023. The exclusion criteria used were literature not available in full text in the database. Based on the selection results, 10 literatures that met the criteria were obtained. The analysis results show that chewing gum can reduce dry mouth, increase saliva flow rate, decrease thirst, and control hypervolemia. The implementation of chewing gum intervention is also said to be easy to do, although it may have side effects that need further investigation. This study concludes that chewing gum can be effective in reducing thirst in hemodialysis patients. Therefore, chewing gum can be integrated into the provision of nursing care for patients undergoing routine hemodialysis.